Influence of Ultrasound on the Rheological Properties, Color, Carotenoid Content, and Other Physical Characteristics of Carrot Puree - Emilia Janiszewska-Turak; Iwona Sitkiewicz; Monika Janowicz (Applied Sciences)
This study aimed to investigate the effect of ultrasonic frequencies (21 and 35 kHz) on the physical properties of carrot puree at different concentrations (9, 12, and 21 °Brix). The viscosity, total soluble content, density, color, and β-carotene content were tested. It was found that the viscosity of the puree, determined with respect to shear rate, concentration, and the use of ultrasonic treatment, indicates that the purees should be defined as shear thinning fluids. Moreover, a decrease in activation energy was observed with the increase in extract and ultrasonic treatment, which may cause changes in the rate of reactions occurring in the tested material. A significant effect of this may be the observed change in the color of the puree after ultrasonic treatment; the increase in frequency from 21 to 35 kHz caused an increase in redness and yellowness and a decrease in lightness, independently of concentration. The most significant color difference was noted in the puree with a 21 °Brix concentration, where a ΔE value of 21 was recorded. In contrast, the ΔE values for the other purees post-treatment remained below 5. The content of carotenoids did not change after sonication, independently of the concentration of carrot puree.